The Effectivity of Parsley (Petroselinum crispum) Extract on The Growth Inhibition of Candida Albicans - Rafinda Naditya Arismunandar; Isniya Nosartika; Brigitta Natania Renata Purnomo; Arlita Leniseptaria Antari (Faculty of Medicine, Diponegoro University, 2021)
Background: Denture stomatitis is a type of Candida-associated infection that mainly affects the palatal mucosa. Candida albicans is one of the normal flora that is considered to be the primary etiologic agent in the pathogenesis of denture stomatitis. Denture decontamination is necessary to prevent denture stomatitis. One method of decontamination is by immersing removable dentures in an antifungal solution. Parsley (Petroselinum crispum) is a medicinal plant showing antifungal activity. Objectives: To determine the effectivity of immersion of acrylic resin Plate in parsley extract on inhibition of growth of Candida albicans. Methods: The effectivity of immersion of heat-cured acrylic resin plates in parsley extract on inhibition of C. albicans growth was tested using an experimental laboratory study with a post-test-only control group design. Thirty samples were divided into 5 groups as 0.01%, 0.02%, and 0.05% parsley ethanol extract, 0.1% sodium hypochlorite, and sterile aquadest. The number of colony forming units per mL was obtained after calculating the colonies on SDA media, allowing the minimum inhibitory concentration (MIC) obtained according to the formula. Results: 0.01% parsley ethanol extract is MIC with a mean of 7.4 CFU / ml, which inhibited the growth of C. albicans by 31.05%. The Kruskal Wallis test (p<0.001) results indicate that there is an effectivity of immersion of acrylic resin plate in parsley extract on inhibition of growth of C. albicans. Conclusions: The immersion of acrylic resin plates in parsley ethanol extract with a concentration of 0.01%, 0.02%, and 0.04% has effectivity on the inhibition of growth of C. albicans.